Diversifikasi Ekonomi di Pulau Bali dalam Perspektif Pariwisata - Victor Kurniawan Yuwono; Fabiola Leoparjo; Devina Irtanto; Kristian Agung Nugraha; Otje Herman Wibowo (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to examine economic diversification on the island of Bali from the perspective of tourism in the technology era. Bali, which has long been heavily reliant on the tourism sector, faces significant challenges due to the COVID-19 pandemic, highlighting its vulnerability to external shocks. The study utilizes both qualitative approaches, gathering data through surveys, interviews, and literature analysis. The findings indicate that the agricultural sector, fisheries, creative industries, and Information and Communication Technology (ICT) show great potential for development as new economic drivers. Organic farming products and sustainable fisheries can meet local needs and offer export opportunities. Creative industries, particularly those digitally based, have garnered high interest from the younger generation and can significantly contribute to Bali's economy. Additionally, ICT can create opportunities in e-commerce, education, technology-based services, and enhance the effective promotion of local products. Local government support is crucial through skills training, capital assistance, and infrastructure development. However, policy implementation is often hindered by complex bureaucracy and budget limitations. The research concludes that economic diversification through the development of these sectors, with appropriate support, can enhance Bali's economic resilience and the well-being of local communities